TRACKING SUICIDAL IDEATION IN EMERGENCY HEATH PROFESSIONALS: SCOPE REVIEW: rastreamento de ideação suicida em profissionais da saúde da emergência: revisão de escopo - da Cunha Aragão Rios Fagundes, Adriane (Revista de Ciências da Saúde Nova Esperança, 2026)
Objective: To identify and map suicide risk instruments for healthcare professionals in hospital emergency care. Method: Scoping review carried out from May to August 2023 based on the recommendations of the Joanna Briggs Institute, according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews guideline. The study protocol was registered in the Open Science Framework. The PCC mnemonic was used: P for Population – health technologies; C for Concept – suicide; C for Context – health personnel. The inclusion criteria were research that responded to the objective of this study, published online, in full, and materials such as books, manuals, protocols and legislation from ministerial bodies or entities specialized in the area and without a time limit, and the exclusion criteria were editorials, theoretical essays and the presence of repeated studies. Results: 120 studies were analyzed, of which 46.61% were aimed at health professionals, 33.33% at health services in general and 30.70% at hospitals, most of which presented soft-hard technologies, demonstrating the prevalence of mental health, impacts and psychosocial factors at work, thus contributing to the verification of management processes. Regarding the years of publications, there was a significant increase after the COVID-19 pandemic. It was found that 59.65% of the studies covered the area of ​​medicine, 21.93% of psychology and 14.91% of nursing. Conclusion: it was observed that there is no suicide risk instrument aimed at the target audience, only studies favoring the verification of circumstances and risk factors for suicidal ideation, requiring the structuring of a prevention instrument.